The effect of supplementing with Saccharomyces boulardii on bismuth quadruple therapy for eradicating Helicobacter pylori: a systematic review and meta-analysis of randomized controlled trials - Chen, Yin; Teng, Tao; Su, Yu; Chen, Wen-Zhong (Frontiers in Medicine, 2024)
Background and objective: It remains uncertain if the addition of Saccharomyces boulardii (S. boulardii) to bismuth quadruple therapy (BQT) recommended in the current guidelines can enhance the Helicobacter pylori (H. pylori) eradication rate and decrease the incidence of adverse events. We therefore conducted a meta-analysis of randomized controlled trials (RCTs) to address this issue. Methods: We performed comprehensive searches in PubMed, Embase, Web of Science, and Cochrane library databases from the inception of the databases through to November 1, 2023. A meta-analysis was conducted to determine the pooled relative risk (RR) with 95% confidence intervals (CI) using a random-effects model. We utilized the revised Cochrane Risk of Bias Tool to assess the risk of bias of included studies. Results: A total of six RCTs (1,404 patients) included in this meta-analysis. The results of the intention-to-treat analysis showed that the combination of S. boulardii with BQT had a higher eradication rate than BQT alone (87.0% versus 83.3%), with a pooled RR of 1.05 (95% CI:1.00-1.10, P = 0.03). In the per-protocol analysis, however, there was no statistical significance between the two groups in the eradication rate (93.7% versus 91.0%, RR = 1.03, 95% CI: 1.00-1.06, P = 0.07). The combination of S. boulardii and BQT had a significantly lower rate of overall adverse events (22% vs 39%, RR = 0.56, 95% CI: 0.44-0.70, P ＜ 0.00001), diarrhea (7.9% vs 25.7%, RR = 0.29, 95% CI: 0.17-0.48, P ＜ 0.00001), constipation (2.9% vs 8.4%, RR = 0.35, 95% CI: 0.14-0.88, P = 0.03) and abdominal distention (4.9% vs 12.7%, RR = 0.41, 95% CI: 0.23-0.72, P = 0.002) than BQT alone. For the assessment of risk of bias, five studies were deemed to have some concerns, while one study was judged to have a low risk. Conclusion: Current evidence suggests that supplementation with S. boulardii in BQT may not have a major effect on the H. pylori eradication rate, but significantly reduces the incidence of overall adverse events , diarrhoea, abdominal distention and constipation. Combining S. Boulardii with BQT can help alleviate symptoms, potentially improving patient adherence.